If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 = x + 22 Reorder the terms: 6 + 4x = x + 22 Reorder the terms: 6 + 4x = 22 + x Solving 6 + 4x = 22 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 4x + -1x = 22 + x + -1x Combine like terms: 4x + -1x = 3x 6 + 3x = 22 + x + -1x Combine like terms: x + -1x = 0 6 + 3x = 22 + 0 6 + 3x = 22 Add '-6' to each side of the equation. 6 + -6 + 3x = 22 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 22 + -6 3x = 22 + -6 Combine like terms: 22 + -6 = 16 3x = 16 Divide each side by '3'. x = 5.333333333 Simplifying x = 5.333333333
| 5x+2y=1625 | | 3x+12=x+34 | | 3x=x+800 | | 10x-9+11x=180 | | Q^2-2Q+3=38 | | .5v+15=-30 | | X+40+2x+10=180 | | 9-4x=3-1x | | 3y-5=5(2y-2)+3 | | 4x/3-7x/6=5 | | 1/(12d)-4/(3d)=15 | | 10sin(30-20)=5 | | 27=(x^2-x)-5 | | 9p-5(p+6)= | | 27=(x^2-y)-5 | | y=3(-13)+33 | | 6x-(x+5)=3x(x-8) | | 5d+2=4d+8 | | 2(x+20)=30 | | 2Y-6=3y+12 | | 9(x-4)=46.8 | | 2(2)/4(13-9(2) | | 6(a+1)=51 | | 26+2x=16 | | 11.2=6c-2 | | 7e-7=61.6 | | 2p=11.6 | | 3(a+5)=33 | | 31=5c-4 | | m*3-2=4 | | a+4c=90 | | 0=x+2x+8 |